A regulamentação dos jogos no Brasil: análise da alteração da natureza jurídica do contrato de jogos e apostas e os impactos sobre a interpretação das relações inter partes nos jogos de habilidade (pôquer) presencial e online - Carvalho, Priscila Cortez de (2023)
The present study proposes to discuss the legislation currently in force and the bills that address the regulation of games in Brazil, from the moralistic justification that for years impacted the theme to the recent currents that seek to bring legal solutions to the activity, in order to allow its commercial exploitation, which might imply a significant modification to the interpretations of the articles of the Civil Code that deal with gaming and betting contracts. For the discussion, it will use the legal repertoire that the poker modality created by challenging the limits of the legal prohibition of gambling and its search for recognition as a game of skill and which has been achieving important worldwide visibility as a sport of the mind